Stress as correlates to optimism among college students - Vicente, Paul Armand R. 4 0 16; 5 (2019)
ABSTRACT: Going to college is a big adjustment a student can encounter. Academic is not the only source of stress in college student caused by school requirements. There is a interpersonal relationship stress because of new people, there are also physical stress because students experience health problems and environmental stress. Being an optimistic person is an important factor for being a studnet. That way they outlook future events in a positive way and can perform better. This study aims to identify the relationship between student stress and optimism among students of Pamantasan ng Lungsod ng Maynila's College of Science. Participants of this study consisted of 278 students of the said college from the university. The researcher used the instrument Student Stress Inventory to identify the level of stress among the respondents and the Life Orientation Test - Revised to identify the level of optimism among respondents. The results showed that most of 278 respondents scored moderate stress and the optimism test shows that most of the respondents scored low optimism. The results also showed that there is no significant relationship between stress and optimism among those who scored high in optimism. In contrast, there is a significant relationship between stress and optimism among those scored low optimism.
Thesis: (B.S. Psychology)- Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2